The Impact of Melatonin and its Agonist on Endothelin-1 Reactivity in Isolated Aorta in Continuous Light and Pinealectomized Rats - Evan B. Othman; Ismail M. Maulood (Zanco Journal of Pure and Applied Sciences, 2023)
The purpose of the present study is to investigate the influence of melatonin and its receptor (MT1, and MT2) agonist (Ramelteon) on vascular endothelin-1 (ET-1) reactivity in isolated aortic rings in continuous light emitting diode (LED) exposure and pinealectomized rats. Materials and Methods: Two sets of experiments were performed in this study. In the first experiment, animals were divided into four groups: (control, continuous LED exposure rats, continuous light + Melatonin administration, and continuous light + Ramelteon administration). In the second experiment, animals were categorized into five groups: Control, rats underwent pinealectomy, pinealectomy + Melatonin administration, pinealectomy + Ramelteon administration, and pinealectomy + a continuous LED exposure. Results: The obtained results indicated that in constant light exposure of the rats for 10 weeks, the ET-1-induced aortic ring contraction was markedly reduced.Conversely, melatonin and its agonist (Ramelteon) markedly elevated the ET-1-induced aortic ring contraction. Neither, melatonin nor its agonist supplementation significantly increased ET-1 Emax. Similarly, in the second experiment after 6 weeks of pinealectomy and pinealectomy with continuous light exposure to rats significantly decreased aortic ring contraction. Moreover, ET-1 Emax significantly and ET-1 efficiency and AUC were slightly elevated in pinealectomy with light exposure group compared to the pinealectomized rats. On the other hand, ramelteon shifted the DRC of ET-1 to the left side. Conclusion: The results suggested that most of the melatonin actions on vascular modulation are due to its binding to MT1and MT2 receptors.